Cephalometric Assessment of Pharyngeal Airway Dimensions in Sagittal and Vertical Growth Patterns - Muhammad Arsalan Mughal, Abdul Jabbar Baloch, Nimra Riar, Dinesh Kumar, Ramesh Lal (Pakistan Journal of Medical & Health Sciences, 2022)
Setting: Determination of patency of airway in sagittal and vertical growth patterns in patients visiting LUMHS Institute of Dentistry, Jamshoro. Methods: This cross-sectional study took place in the Orthodontic Department, Institute of Dentistry, LUMHS Jamshoro. Patients in the age group of 12 to 28 years were included. All subjects were categorized into two groups: Group 1 consists of patients with vertical growth, and Group 2 consists of patients with horizontal growth. Measurements were done by McNamara analysis; the skeletal type was analyzed using ANB, FMA, and SN-GOGN measurements were plotted on the Y-axis, measuring the angle between the S-N plane and sella-gnathion. Results: A total of 62 patients were studied; their mean age was 20.74+3.36 years. The majority were females 77.4% and males 22.6%. two groups were made according to growth patterns, group 1 consisted of vertical growers and group 2 was of horizontal grower patients. 37.1% of patients were found to have an obstructive lower pharyngeal airway. Mean ANB, FMA, Y-Axis, SN-GOGN, upper pharyngeal airway, and lower pharyngeal airway was 5.42±3.52 degree, 27.90±7.93 degree, 66.31±6.56 degree, 34.24±7.95 degree, 14.5±2.24 mm and 9.2±2.04mm respectively. The results show a positive and negligible correlation between ANB and pharyngeal airways. Conclusion: There was a positive and negligible correlation between sagittal growth patterns and pharyngeal airway, with class II cases having obstructive pharyngeal airway and class III cases having patent pharyngeal airway. Keywords: Patency of Airway, Sagittal, Skeletal Discrepancies, Vertical